(untitled) (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2025)
This article analyzes the issues associated with the concept of the head of the investigative body in criminal proceedings. Additionally, it thoroughly examines problems related to the procedural status of the head of the investigative body in criminal proceedings (including the scope of authority of the heads and deputy heads of investigative departments, divisions, units, and groups, as well as their distinguishing features). Furthermore, the article analyzes the work of national and foreign scholars and relevant legislation.